KAM-PaY: Closed Wallet with SQL-Technology and Biometric Authentication (Journal of Information Technology and Digital World, 2024)
Closed Wallet is a novel database collection system designed to securely gather and manage user data using SQL technology. This system addresses the growing concern for data privacy and security by implementing robust authentication methods and access controls. Through SQL queries, Closed Wallet efficiently retrieves and stores user information while adhering to stringent privacy regulations. The proposed KAM-Pay (Kamaraj payment), an implementation of the closed e-wallet system for the college canteen in Kamaraj Engineering college, is being developed using Visual Studio. Furthermore, the biometric authentication in proposed work ensures the data integrity and confidentiality, safeguarding sensitive information from unauthorized access.
Keywords: Digital Payment; Security; E-Wallet; Finger Print Sensor; Visual Studio